2021
DOI: 10.1136/bmjopen-2020-043349
|View full text |Cite
|
Sign up to set email alerts
|

Risk of falls in 4 years of follow-up among Chinese adults with diabetes: findings from the China Health and Retirement Longitudinal Study

Abstract: ObjectivesThis study was to determine the incidence of falls and identify baseline factors increased risk for incident falls over time among people with diabetes.DesignThis study was a secondary analysis using the baseline and 4 years of follow-up data from the China Health and Retirement Longitudinal Study (CHARLS).SettingA nationally representative survey of 17 500 Chinese residents aged 45 years and older were recruited in the baseline national survey in 2011. These participants were followed up every 2 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In addition to daily activities, social activity can also improve physical and mental health and reduce the risk of falls [30,31]. We included participants from community centers, community colleges, and local dementia community centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to daily activities, social activity can also improve physical and mental health and reduce the risk of falls [30,31]. We included participants from community centers, community colleges, and local dementia community centers.…”
Section: Discussionmentioning
confidence: 99%
“…They were all socially active, but those with lower education levels had a higher number of falls in our study within the socially active population. A previous 4-year cohort study of a population aged 45 years and over also found that participants with fall incidents had lower education levels [30]. Elderly people with lower education levels may have difficulty grasping fallprevention information [32]; therefore, a fall-prevention program is warranted in this group of people.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also have showed a lower socioeconomic status to be a major risk factor for falls 7 . Health-related factors such as functional limitations, weak handgrip strength, chronic diseases such as diabetes or bone and joint diseases are also associated with a higher prevalence of falls [8][9][10] . Similarly, sleep problems are a major risk factor for falls.…”
mentioning
confidence: 99%
“…Date for falls and frequency of falls was unavailable as well. Although this method has been used in previous studies (49)(50)(51)(52)(53), possible misclassification of sensory loss status or inaccurate reports may lead to bias. Also, the causal effects of sensory loss on falls could not be reached according to the present study.…”
Section: Strengths and Limitationsmentioning
confidence: 99%